Perishable Food RFID Traceability System with IoT Sensors - Nur Afiqah Hamizah Kamarudin,; Hairulazwan Hashim, (Progress in Engineering Application and Technology, 2022)
The food industry is usually rated by the quality of the goods and products served by the company. Thus, maintaining quality plays a crucial role. In recent years, consumers are starting to take care of their food quality intake in order for greater health. This project paper will describe “Perishable Food RFID Traceability System with IoT Sensors” designed by using RFID and IoT devices to precisely identify the surrounding condition and location of the perishable food to maintain the safety and quality of perishable food during transportation and storage. Tracking real-time location and the ambiance temperature could ensure the logistics can achieve the objectives and also ensure the reliability of the system to maintain food quality.